(untitled) (Research, Society and Development, 2021)
Objective: to analyze the sociodemographic variables and lifestyle habits associated with diabetes in men. Methodology: this is an observational, descriptive, sectional epidemiological study. Data collection took place in the year 2019. The study population consisted of men residing in the municipality of Bananal, located in the interior of the State of São Paulo, in the historic valley circuit of faith in the Paraíba Valley. The study sample totaled 386 subjects. Results: according to the regression model used, and after adjusting for potential confounding variables, the following variables maintained a statistically significant difference and risk for the outcome studied: sleep (p = 0.032, PR = 2.30 - 95% CI = 1.074 - 4,937); treatment for SAH (P = 0.02, PR = 0.13 - 95% CI = 0.37 - 0.472); consultation frequency (p = 0.010, PR = 0.31 - 95% CI = 0.127 - 0.755). Conclusion: from this study it was possible to identify that being single, family provider, not consuming fruit, checking blood glucose, not adhering to treatment for systemic arterial hypertension and sleeping less were related to the presence of DM in men using SUS. This study becomes relevant because it addresses the association between sociodemographic variables and diabetes lifestyle among SUS users, since there is little research in this area regarding the male audience.